Exploring the Moderating impact of ICT Infrastructure on Trade Openness-Sectoral Growth Nexus in Sub-Saharan Africa (SSA) - Oshinowo, Bamidele O.; Adelowokan, Oluwaseyi A.; Siyanbola, Adedamola A.; Ogede, Jimoh S. (NIU Journal of Humanities; Vol 10 No 3 (2025): NIU Journal of Humanities, Vol. 10 No. 3, September 2025, 2025)
This study examines the moderating role of Information and Communication Technology (ICT) infrastructure in the relationship between trade openness and sectoral growth in Sub-Saharan Africa (SSA). Using balanced panel data for 26 SSA countries from 1992 to 2023, sourced from the Penn World Table, African Development Bank, International Monetary Fund, and World Bank Development Indicators, the analysis employs the Pooled Mean Group–Autoregressive Distributed Lag (PMG/ARDL) approach. Results show that, in the long run, trade openness has a negative and significant impact on agricultural, industrial, and, in most cases, service sector growth. ICT infrastructure positively influences industrial and service sectors but has limited direct effects on agriculture. Interaction terms between trade openness and ICT variables are predominantly negative and significant, suggesting that higher trade openness reduces the growth-enhancing effects of ICT. In the short run, trade openness, ICT, and their interactions are largely insignificant across sectors. Foreign direct investment emerges as a consistent short-term driver of agricultural growth, while labour force dynamics significantly affect short-term industrial and service performance. The findings underscore the need for policies that integrate ICT expansion with complementary infrastructure, skills development, and targeted trade strategies. Strengthening domestic capacity, enhancing productivity, and ensuring inclusive access to ICT can enable trade openness to translate into sustainable growth across sectors in SSA.